PENGARUH MINYAK ATSIRI KULIT BUAH JERUK NIPIS (Citrus aurantiifolia (Christm.) Swingle ) TERHADAP LARVA Aedes aegypti - Tonang, Maswa Ruslan; Hasnaeni, Hasnaeni; Handayani, Virsa (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Lime peel (Citrus aurantiifolia (Christm.) Swingle) belongs to the Rutceae family. It contains essential oil, limonene and limonoid, with the potential as a larvicides. The research aimed to determine the effect of essential oil of lime peel against Aedes aegypti larvae. The method used was steam distillation to obtain the essential oil. The activity test was conducted by determining LC50 at the concentration of 250 ppm, 500 ppm, and 1000 ppm. Each concentration was tested for 10 Aedes aegypti mosquito larvae. The result showed that the essential oil of lime peel had the effect against Aedes aegypti larvae with the LC50 value of 151.356 µg/mL